Epigallocatechin-3-gallate protects against osteoarthritis-induced chondrocytes dysfunction by regulating PLa2g2a - Dai, Mengyuan; Shi, Jing; Wang, Tao; Wan, Sha; Fan, Chen; Wang, Siyu; Chen, Siyuan; Shang, Jiaojiao; Kong, Qingquan (Frontiers in Pharmacology, 2025)
BackgroundOsteoarthritis (OA) is a degenerative joint disease characterized by cartilage erosion, subchondral bone remodeling, and synovial inflammation. OA progression is driven by an imbalance between anabolic and catabolic activities in the cartilage extracellular matrix (ECM). Identifying molecular targets involved in chondrocyte (responsible for ECM homeostasis in OA) dysfunction is therefore essential for developing effective OA treatments. Notably, epigallocatechin-3-gallate (EGCG), a polyphenolic compound derived from green tea, is a known pan-assay interference compound (PAINS), which may produce non-specific in vitro effects (e.g., protein binding, redox interference) that challenge the interpretation of its pharmacological relevance. Thus, multi-dimensional validation (in vitro + in vivo + transcriptomic) is critical to mitigate such limitations.MethodsWe investigated the effects of epigallocatechin-3-gallate (EGCG), a polyphenolic compound derived from green tea, on OA-induced dysfunction in chondrocytes. Primary chondrocytes, extracted from the knee joints of rats and constructed an OA model via IL-1β stimulation, observed cell viability and morphology upon EGCG treatment. Transcriptomic analysis was conducted to screen for differentially expressed genes. Subsequently, an OA model in rats was induced by intra-articular injection of monoiodoacetic acid (MIA), and EGCG was administered for OA treatment to validate the expression of the differentially expressed genes.ResultsEGCG could reduce reactive oxygen species (ROS) levels and decreased the expression of inflammatory cytokines IL-β, MMP13, and TNF-α. Transcriptome analysis identified differentially expressed genes, and network pharmacology pinpointed Pla2g2a as a key target of EGCG. Molecular docking studies confirmed a strong binding affinity between EGCG and Pla2g2a. OA model demonstrated that EGCG treatment significantly promoted cartilage repair and increased Pla2g2a expression. In vivo experiments demonstrated that EGCG treatment significantly promoted cartilage repair and upregulated Pla2g2a expression, consistent with in vitro and transcriptomic findings—suggesting the observed effects are not solely due to PAINS interference.ConclusionThese findings underscore the therapeutic potential of EGCG in OA management via antioxidative, anti-inflammatory properties, and Pla2g2a-mediated modulation. Notably, the consistency across in vitro, in vivo, and transcriptomic data supports the biological relevance of EGCG’s effects, despite its PAINS characteristics.